Dual HIV risk and vulnerabilities among people who inject drugs in Iran: Findings from a nationwide study in 2020 - Soheil Mehmandoost; Mehrdad Khezri; Niloofar Aghaali; Mostafa Shokoohi; Ali Akbar Haghdoost; Fatemeh Tavakoli; Hamid Sharifi; Mohammad Karamouzian (BMC, 2024)
Abstract Introduction People who inject drugs (PWID) are a key population at risk of HIV in Iran. We measured the prevalence and covariates of HIV-related risk behaviours among PWID in Iran. Methods We conducted a respondent-driven bio-behavioural surveillance survey among PWID from July 2019 to March 2020 in 11 major cities. We assessed PWID's recent (i.e., last three months) HIV-related risk behaviours using a four-level categorical variable: Only unsafe injection (i.e., sharing needles/syringes or injecting equipment), only unsafe sex (i.e., unprotected sex), dual HIV risk (i.e., both unsafe injection and unprotected sex), and safe injection and sex. Data were summarized using RDS-weighted analysis. Multinomial logistic regression models were built to characterize HIV-related risk behaviours and relative risk ratio (RRR) with 95% confidence interval (CI) were reported. Results Overall, 2562 men who inject drugs (MWID) were included in the regression analysis. The RDS-weighted prevalence of dual HIV risk was 1.3% (95% CI: 0.8, 1.9), only unsafe injection was 4.5%, and only unsafe sex was 11.8%. Compared to the safe injection and sex group, dual HIV risk was significantly and positively associated with multiple partnership (RRR = 15.06; 3.30, 68.73). Only unsafe injection was significantly associated with homelessness in the last 12 months (RRR: 3.02; 95% CI: 1.34, 6.80). Only unsafe sex was significantly associated with multiple partnership (RRR = 6.66; 4.27, 10.38), receiving free condoms (RRR = 1.71; 1.01, 2.89), receiving free needles (RRR = 2.18; 1.22, 3.90), and self-received risk for HIV (RRR = 2.51; 1.36, 4.66). Moreover, history of HIV-testing in the last three months was significantly associated with only unsafe injection (RRR = 2.71; 1.84, 3.80). Among the 90 women who injected drugs, none reported dual HIV risk behaviours. Discussion and conclusions While the low prevalence of dual HIV risk among PWID is encouraging, unprotected sexual practices among PWID is concerning. Expanding sexual health education and care services as well as tailored interventions aimed at reducing high-risk sexual activities among PWID are warranted. Additionally, tackling potential misperceptions about risk of HIV transmission among PWID in Iran is warranted.